Pendampingan Dan Pembuatan Izin Berusaha Melalui Aplikasi Online Single Submission Bagi Pelaku UMKM Di Desa Nglebak - Mu'tasim Billah; Kirana Aurelia Julianne Maharani; Nur Rochmah Yulianita; Reynaldi Krisvinus Pasaribu; Wahyu Arrofiq (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Over time, in Jombang District, Bareng District, there have been a large number of business actors. The legality of doing business, namely making NIB, is something that many business actors are not currently penalized for. While the NIB itself determines the operations of business actors. The legality of the company is only one of the many benefits of having an NIB. The aim of this community service project is to raise awareness no matter how small an NIB permit is by using technology, which will ultimately make MSMEs step up their game. This service approach involves teaching the client how to use the OSS program to create an online NIB. A simple tool, namely the cellphone of each MSME actor, is used to direct them to provide the necessary information in the form of their KTP and business certificate. Actors can print an output in the form of an NIB certificate accompanied by a presenter as a result of this support. It is believed that initiatives like this in community service will help partners find answers to their problems.